Estudio de la producción de cacao orgánico en la Provincia de Los Ríos, con énfasis en la exportación - Flores Remache, Jahaira Michel (2021)
This document study the production of organic cocoa in the Province of Los Ríos, with an emphasis on export. Cocoa is one of the main export products of our country, therefore it is necessary for government agencies to support small and medium producers of organic cocoa, in order to obtain higher production and yield, for export purposes. The conclusions determine that Ecuador has not developed large-scale organic cocoa production, taking into account that internationally it has a growing demand, due to the trends of leading a healthier and chemical-free life. Small producers that still produce organic cocoa do not have sufficient knowledge of the excellent quality of their products, so they are limited to selling organic cocoa at the price that chemically treated cocoa is regularly sold; The current producers of Ecuadorian organic chocolate have their own plantations due to the shortage of organic raw material within the country and there is no information material on organic cocoa in the province of Los Ríos.